Reaching Out: Gingoog City's Total Integrated Development Approach (G-TIDA) - Virginia S. Pineda; Clark Clarete (Philippine Institute for Development Studies (PIDS), 1998)
This paper is one of eight case studies in the health sector conducted under the project "Population and Urbanization: Managing the Urbanization Process Under a Decentralized Governance Framework" jointly undertaken by the Philippine Institute for Development Studies, National Economic and Development Authority and Development Academy of the Philippines. This paper is a case study on Gingoog City recommended by NEDA-Region X as a model city for health. Gingoog's G-TIDA has been featured in the DOH-Health and Management Information System publication.
Keywords: 330; health sector